Phenotypic symptoms of conjugate tissue dysplasia in persons of young age with mitral valve prolapse. - M. A. Kuznetsova (Medičnì Perspektivi)
In connection with the significant increase in complications, developing in young people with mitral valve prolapse (MVP), the study of phenotypic signs and peculiarities of the formation of this pathology is topical. A survey of 135 young people aged 17-25 years with mitral valve prolapse was conducted. The patients were examined by specialist-doctors: neuropathologist, otorhinolaryngologist, surgeon, traumatologist and oculist to exclude organic pathology; the distribution of phenotypic signs of connective tissue dysplasia depending on degree of MVP was evaluated. It was established that in young people with MVP of 2nd degree external and visceral manifestations of connective tissue dysplasia occur significantly more often than in persons with MVP of 1 degree.